Metode Kurva Batasan Energi Untuk Evaluasi Resiko Arc-flash Pada Sistem PLTU - Wiharya, Chandra; Priya Surya Harijanto; Farrasdito Aulia Rizky (Elposys: Jurnal Sistem Kelistrikan, 2024)
In an effort to determine the Personal Protective Equipment (PPE) required to protect against arc-flash hazards based on IEEE Std. 1584-2002, a simplified analysis technique was used with the energy limit curve method. The problem addressed was the potential inaccuracies in determining the required PPE level and maximum flash-protection distance when the traditional method does not precisely calculate the incident energy level and flash-protection limit. The purpose of this study was to evaluate a method that could be applied to various types of overcurrent protective devices in electrical systems, thus simplifying the arc-flash analysis. The method involved using the energy limit curve, which allows for quicker determination of the necessary PPE by plotting relay/fuse curves into the energy limit curve. This approach was implemented and tested at PLTU Paiton Unit 7 (PT. POMI). Important findings indicated that the energy limit curve method significantly reduced the time required to determine the appropriate PPE category compared to the IEEE 1584-2002 standard. The results showed that the process of determining the PPE category was more efficient, with fewer data requirements and shorter calculation times. The implications of this research suggest that the energy limit curve method can simplify arc-flash calculations for large industries with numerous buses, enhancing the overall safety protocols by providing a faster and potentially more accurate means of assessing arc-flash hazards and PPE requirements.